Coronal tibiofemoral subluxation in patients with osteoarthritis was corrected after total knee arthroplasty. Issue 37 (16th September 2022) - Li, Ruibo; Fu, Peng
Abstract : The objective of this study was to investigate the effect of preoperative coronal tibiofemoral subluxation (CTFS) on postoperative mechanical alignment in patients undergoing total knee arthroplasty (TKA) for primary knee osteoarthritis (OA) and to investigate whether TKA can correct preoperative CTFS. We hypothesized that TKA would correct CTFS in patients with knee OA. A retrospective analysis of 102 patients with knee OA who underwent TKA was performed. The preoperative and postoperative CTFS and mechanical alignment were measured and compared. At the same time, the baseline values of CTFS and mechanical alignment in "normal" patients were measured and compared with those in the operation group. Eighty patients were eventually enrolled in the study. Mechanical alignment was corrected from 7.3 ± 5.2°, preoperatively, to 1.6 ± 2.3° postoperatively, while the tibiofemoral subluxation was corrected from 5.3 ± 2.6 mm, preoperatively, to 2.3 ± 2.7 mm postoperatively. There was no significant correlation between preoperative CTFS and gender ( r = 0.03), BMI ( r = −0.09), age ( r = 0.05), or preoperative mechanical alignment ( r = 0.09). In addition, there was no correlation between the degree of correction of CTFS and the degree of correction of overall mechanical alignment ( r = 0.14). The difference between the value for CTFS in the "normal" patients and the preoperative value for arthritis cohorts were statistically significant ( P = .004). However, no significant difference was appreciated between the value for CTFS in the "normal" patients and the postoperative value for TKA cohorts ( P = .25). Preoperative CTFS does not affect postoperative mechanical alignment. Excellent TKA can correct preoperative CTFS in OA patients to reduce prosthesis wear and improve postoperative patient satisfaction.